1991
DOI: 10.1021/ma00018a031
|View full text |Cite
|
Sign up to set email alerts
|

Rheology and dynamics near phase separation in a polymer blend: model and scaling analysis

Abstract: The dynamics of low molecular weight polymer mixtures, in terms of concentration fluctuations near a critical point, in the homogeneous region, has shown a nonlinear behavior in a number of physical properties.1-2 For high molecular weight mixtures, i.e., polymer blends and block copolymers, most of the studies dealt with the dynamics of phase separation and spinodal decomposition and its incidence on the scattering properties of these mixtures.3 For the viscoelastic properties, Bates,[4][5][6] Gouinlock and P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
127
0

Year Published

2003
2003
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 119 publications
(139 citation statements)
references
References 7 publications
12
127
0
Order By: Relevance
“…[17,19,[34][35][36] For quantitative studies of phase separation in binary PVME/PS blends [37] and ternary PVME/PS/HNPs nanocomposites, [35] the mean field theoretical approach of Ajji and Choplin [38,39] has been demonstrated to be very reliable for determining phase separation temperatures from the T-dependence of the bulk elastic modulus (G´) and the bulk loss modulus (G´´) at small strain and very low shear rates (i.e. in the linear regime).…”
Section: Resultsmentioning
confidence: 99%
“…[17,19,[34][35][36] For quantitative studies of phase separation in binary PVME/PS blends [37] and ternary PVME/PS/HNPs nanocomposites, [35] the mean field theoretical approach of Ajji and Choplin [38,39] has been demonstrated to be very reliable for determining phase separation temperatures from the T-dependence of the bulk elastic modulus (G´) and the bulk loss modulus (G´´) at small strain and very low shear rates (i.e. in the linear regime).…”
Section: Resultsmentioning
confidence: 99%
“…Ajji and Choplin [41] found that effects of phase separation on G 0 were more pronounced than on G 00 : Scholz et al [37] reported that the values of the dynamic moduli at high v ðv . 10 rad=sÞ for the immiscible blend of PP/Polyamide 6 were intermediate between those of PA6 and PP.…”
Section: Introductionmentioning
confidence: 99%
“…Near g the time-temperature superposition principle ( -) is not valid [205], but it is obeyed for deutereous PS below LCST(PS) 40 C [202]. However, at higher temperatures their relaxation times deviate with a magnitude dependent on the molecular weight ratio [206][207][208][209][210]. Kim and Son [211] plotted log versus log for different compositions and temperatures; at 10 wt% PS the data formed a linear dependence independent of stretching from below to above LCST.…”
Section: Generalmentioning
confidence: 99%
“…Since blend morphology and kinetics of phase separation are expected to affect the rheological functions, great care is needed in collecting rheological data and interpreting them [223,224]. The two polymers have widely different glass transitions, g (PS) 373-378 and g (PVME) 227-247 K. The g of their blends shows a negative deviation from additivity, that is, PVME acts as a macromolecular solvent/plasticizer of PS, especially when the ratio of molecular weights, w (PS)/ w (PVME), is large [202][203][204][205][206][207][208][209]. When the ratio is about 2, a passage through the phase separation region affects but not , while for the ratio <1 the moduli increase upon entering the phase separation region.…”
Section: Influence Of Thermodynamics On Rheologymentioning
confidence: 99%
See 1 more Smart Citation